(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The research aims to study and evaluate some geotechnical properties of the sediments within the Kirkuk Irrigation Project, starting from the Al-Dibs Barrage to the end of the Tuz Khurmatu district. Geotechnical tests were conducted on six stations representing these sediments. The tests revealed that the project sediments exhibit varying grain sizes, indicating that the soil is heterogeneous in its properties. Based on the plasticity chart, some samples were classified as low-plasticity clay (CL), while most samples were classified as low-plasticity silt (ML). The specific gravity values ranged between 2.66 and 2.74. Chemical analyses showed that the gypsum content, total dissolved salts (TDS), organic matter, and sulfate content ranged between 5.33–13.23%, 7.13–15.18%, 0.12–0.65%, and 0.9–4.7%, respectively. The pH values ranged from 7.94 to 8.3. These high levels, particularly gypsum and TDS, significantly affect the engineering properties of the sediments. Geotechnical tests indicated that cohesion values ranged between 2.2 and 14.9 kg/cm². Cohesion values increase with a higher fine particle content and decrease with increased moisture content and coarse particle content. The internal friction angle ranged between 8° and 22°, and it is influenced by the plasticity index and the proportion of coarse particles. In conclusion, the sediments in the study area can generally be utilized for certain engineering purposes after proper treatment.